Predictors of family‐based treatment for adolescent eating disorders: Do family or diagnostic factors matter?. Issue 2 (1st December 2022) - Datta, Nandini; Hagan, Kelsey; Bohon, Cara; Stern, May; Kim, Bohye; Matheson, Brittany E.; Gorrell, Sasha; Le Grange, Daniel; Lock, James D.
Abstract: Objective: Misconceptions around which patients will and will not benefit from family‐based treatment (FBT) for adolescent eating disorders (EDs) limit referrals and access to this treatment modality. The present study explored whether common demographic and clinical factors that may prevent referral to FBT predict treatment outcomes in adolescent anorexia nervosa (AN) and bulimia nervosa (BN). Method: The following predictors of treatment outcomes were assessed: baseline family and diagnostic factors (socioeconomic status, comorbidity, illness duration, parent feelings of self‐efficacy, family status, prior treatment, sex and prior hospitalizations) in a combined sample of adolescents receiving FBT compared to those randomized to other treatment conditions, across six clinical trials in the United States and Canada (total n  = 724, ages 12–18, 90% female across both diagnoses). AN and BN samples were examined separately. Results: Any prior ED treatment emerged as the only predictor of outcome in AN and BN, such that having no prior treatment predicted better outcomes in FBT for AN, and in both FBT and other treatment modalities for BN. No other sociodemographic or clinical variables predicted outcomes for AN or BN in FBT or in other evidence‐based treatment modalities. Conclusions: The findings of this exploratory analysis suggest that commonly assumed factors do not predict outcome in FBT. Specifically socioeconomic and demographic factors or clinical variability in families seeking treatment do not predict treatment outcomes in FBT, or other evidence‐based treatment modalities, with the exception of prior treatment. Providers should consider referring to FBT even when these factors are present. Public Significance: This manuscript reports that commonly assumed family, sociodemographic and diagnostic factors do not predict outcome in FBT or other evidence‐based treatment modalities, with the exception of prior treatment. This data may be helpful for providers when considering referrals to FBT in the context of variability in these variables.